2019
DOI: 10.1002/uog.20252
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of non‐visualization of fetal gallbladder on second‐trimester ultrasound: cohort study and systematic review of literature

Abstract: Objectives To investigate the ultrasound characteristics and outcome of fetuses with non‐visualization of the fetal gallbladder (NVFGB) followed in our tertiary university hospital, and to provide a comprehensive review of the literature on prenatal findings and outcome of NVFGB. Methods NVFGB was defined as non‐visualization of the gallbladder on two targeted ultrasound examinations performed within a 1‐week period. First, we reviewed the medical records of NVFGB cases managed in our center over a 9‐year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…None of these eight fetuses had a CF or a CFTR-RD genotype. A recent publication of 18 cases of NVFGB showed that in about 70% of cases, gallbladder was visualized later in pregnancy or at birth as was confirmed by a meta-analysis reporting on 273 cases [ 31 ]. According to this meta-analysis, the benign condition of gallbladder agenesis was observed in 25% of cases with previous NVFGB, and a severe condition was found in about 10% cases (1.9% chromosomal abnormalities, 4.8% biliary atresia and 3.1% CF cases).…”
Section: Discussionmentioning
confidence: 83%
“…None of these eight fetuses had a CF or a CFTR-RD genotype. A recent publication of 18 cases of NVFGB showed that in about 70% of cases, gallbladder was visualized later in pregnancy or at birth as was confirmed by a meta-analysis reporting on 273 cases [ 31 ]. According to this meta-analysis, the benign condition of gallbladder agenesis was observed in 25% of cases with previous NVFGB, and a severe condition was found in about 10% cases (1.9% chromosomal abnormalities, 4.8% biliary atresia and 3.1% CF cases).…”
Section: Discussionmentioning
confidence: 83%
“…A systematic review by Di Pasquo concluded that the positive and negative predictive values of decreased concentrations of gamma-glutamyl transpeptidase and intestinal alkaline phosphatase in amniotic uid for predicting biliary atresia or cystic brosis before 22 gestational weeks were 69%-100% and 94%-100% respectively. However, the results for amniotic uid after 22 gestational weeks demonstrated reduction in both positive (62%) and negative (88%) predictive values [13] . Therefore, there are still limitations in diagnosis by amniotic uid biomarkers.…”
Section: Discussionmentioning
confidence: 89%
“…Studies indicate that most NVFGB during pregnancy is temporary. In the study by Di Pasquo, et al, 75% of foetal gallbladders were located during later follow-ups [13] . In our study, 69% (34/49) of foetal gallbladders were located after subsequent followups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In most cases, nonvisualization of gallbladder is a transient finding, so a subsequent scan is crucial. If persistent, the majority of cases, especially isolated ones, are benign, however, it raises the concern of cystic fibrosis, biliary atresia, and aneuploidy 52 (Figure 7, Table 1).…”
Section: Nonvisualization Of Gallbladdermentioning
confidence: 99%